Improving Students Activity and Students Mathematic Learning Outcomes by Using Contextual Teaching and Learning - Zaki Ghufran (Universitas Islam Jember, 2020)
The purpose of the research to describe the using of Contextual Teaching and Learning for increasing the students’ activities and the students learning outcomes, to describe the students’ activities during the application of Contextual Teaching and Learning, and to describe the students learning outcomes after the using of Contextual Teaching and Learning. The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VIIB at SMP Negeri 2 Maesan Bodowoso. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is increased activity and mathematical student learning outcomes.Keywords: CTL, students activity, and mathematical learning outcome